Influência da fibrose hepática na progressão da periodontite apical. análise histológica e imunoistoquímica para interleucina-6 em ratos Wistar. - Azevedo, Julia Pantaroto de [UNESP] (2020)
The aim of this study was evaluate the effect of Liver Fibrosis (LF) on the development of Apical Periodontitis (AP), analyzing the behavior of interleukin 6 (IL- 6). Forty Wistar rats were used, divided into 4 groups (n = 10): Group C - control rats; Group LF - rats bearing LF; Group AP - rats bearing AP; LF + AP group - rats bearing LF and AP. LF was induced chemically and surgically. Carbon tetrachloride (CCl4) was administered at a dosage of 0.2 ml / 100 g body weight, twice weekly, intraperitoneally, and throughout the experiment (60 days). After 30 days from the beginning of the drug administration, a surgical procedure for ligation of the bile duct was performed, and the AP was induced by pulp exposure of the first and second right and upper molars. After another 30 days, the rats were euthanized and the jaws were collected for analysis under light microscopy. The liver tissue was analyzed in H.E and PSR staining to prove the induction of liver fibrosis and the processed jaws for histological, histometric, and immunohistochemical analysis for IL-6. The results obtained were analyzed and compared by specific statistical tests for each case with a significance level of 5% (p <0.05). FH was confirmed by histological analysis of the liver of the FH and PA + FH groups, which presented necrotic hepatocytes, vascular disorganization, and intense deposition of collagen fibers in the hepatic parenchyma forming fibrosis bridges. As for apical periodontitis, a moderate inflammatory infiltrate was observed in the PA group and intense in the PA + FH (P <0.05). Histometric analysis revealed a greater area of periapical bone resorption in the PA + FH group compared to the PA group (P <0.05). The pattern of immunostaining of the cytokine IL-6 was higher in the PA + FH groups when compared to the PA (P <0.05). It is concluded that FH exacerbates the inflammatory infiltrate and bone resorption of apical periodontitis as well as the increase in IL-6.